Dietary resource overlap among three species of frugivorous bat in Costa Rica - Maynard, Lauren (2019)
The maintenance of biodiversity in tropical forests is thought to be dependent on fine-scale mechanisms of niche partitioning that allow species to coexist. This study examined whether three species of short-tailed fruit bat that co-occur at a lowland tropical forest site in Costa Rica (Carollia castanea, C. perspicillata, C. sowelli) avoid inter- and intraspecific competition through dietary specialization on species in the genus Piper. First, dietary composition was examined using faecal samples (N = 210), which yielded three main findings: (1) bat species and sexes vary in overall reliance on fruits of Piper, with a higher percentage of seeds of Piper detected in the diets of C. castanea (98.2%) and females (91.5%); (2) adults and juveniles partition species of Piper by habitat, with a lower percentage of mid- to late-successional species of Piper detected in adults (20.8%); and (3) overall, there is a strong dietary overlap among and within the three species of Carollia. Second, controlled choice experiments were conducted with individual bats (N = 123) to examine preferences for different species of Piper. These results indicated few differences in Piper preference based on bat species, sex, age class or reproductive status, suggesting preference is not the primary mechanism shaping the observed differences in dietary composition. Overall, the dietary composition and preference similarities suggest there is strong competition both among and within the three species of Carollia for food resources.